Detecting the impacts on UK sublittoral rock communities of resuspended sediments from fishing activity. (June 2021) - Hinchen, Hayley; Gallyot, Jennifer; Carter, Anita; Ferguson, Matthew; Webb, Karen; Nelson, Mike; Jenkins, Chris
Highlights: Resuspended sediments from fishing modelled using Vessel Monitoring System data. Epibenthic response to resuspended sediments is masked by univariate metrics. Threshold Indicator Taxa Analysis shows community change at low pressure level. Frequency of occurrence recommended to detect change in sublittoral rock community. Genus Caryophyllia and cup-like sponges show strong negative response to pressure. Abstract: Sublittoral rocky reef habitats host important ecological communities in UK waters, but their ecological condition is difficult to monitor. Monitoring methods based on seabed imagery data are prone to inconsistencies in both the identification and enumeration of species, which is a major hurdle in detecting meaningful ecological change. To overcome this problem, our study used a single monitoring dataset, collected using one standard method at the Pisces Reef Marine Protected Area (MPA) in 2016. We identified which method of data extraction from seabed imagery is best able to detect change along a gradient of anthropogenic resuspended sediments, which represents a pressure on the epifaunal community. We modelled the spatial distribution of the pressure, caused by nearby fishing activity, using an approach based on individual Vessel Monitoring System (VMS) ping data, rather than spatially homogenised data aggregated to a grid cell. We found that up to 22% of the biological variability across the three reef areas within the MPA is explained by the measured and derived environmental variables. The response of the epibenthic community at Pisces Reef MPA to the resuspended sediments pressure gradient is masked by commonly used univariate metrics such as species diversity and abundance of individuals. Conversely, a Threshold Indicator Taxa Analysis (TITAN) identifies community-level change caused by a low level of modelled resuspended sediments pressure. We found that a 0.05 decimal degree grid cell of seabed within 1 km of the MPA boundary, swept by demersal fishing gear as little as five times per year on average, can elicit such a community response. The data extraction metric best able to detect this change in the sublittoral rock community is the frequency of occurrence of taxa in images with an average field of view of 0.7 m 2, using a 25-cell grid. More traditional metrics extracted from seabed imagery, such as raw counts and percentage cover estimates, are less sensitive to detecting such community change. The TITAN also identified taxon-level responses to the pressure gradient that could be considered for future monitoring programmes. The solitary coral genus Caryophyllia and cup-like sponges show a sharp and strong negative response to pressure exposure, and could represent a starting point for a future monitoring programme of UK sublittoral rock habitats. The implications for future monitoring are discussed, including survey design, environmental and biological data collection and improved pressure modelling.